1989
DOI: 10.1177/004051758905900505
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Compression Hysteresis of Fibrous Assemblies

Abstract: An analysis of a fibrous assembly at large deformations has been explored as a means of predicting the compressional behavior, especially the compression hysteresis. The essential principle is to classify all the fiber contact points in the assembly as either slipping or nonslipping, so they can be dealt with separately. The compressional modulus and Poisson's ratio are derived and shown to be dominated by the mechanical properties and the directional distribution of the individual fibers within the assembly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 7 publications
1
90
1
Order By: Relevance
“…cycle, then a certain part of the deformation is not recovered when the load is released, and the thickness under given load decreases for each successive cycle. This hysteresis behavior is studied in [28]. Typically after the third cycle the differences between the subsequent cycles become negligible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…cycle, then a certain part of the deformation is not recovered when the load is released, and the thickness under given load decreases for each successive cycle. This hysteresis behavior is studied in [28]. Typically after the third cycle the differences between the subsequent cycles become negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Compression behavior of random fibrous assemblies is controlled by a number of factors as fiber bending rigidity and friction and fiber orientation and density in an assembly. Descriptive and to certain extent predictive theories for compression resistance can be found in [28,29]. So far as the listed properties of two different fiber assemblies are close, one can expect that the compression response of these assemblies is close as well; the differences of these properties lead to different compression resistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, Grosberg and Smith 34,91 have shown that if one pulls a fiber from a twistless sliver, the withdrawal force WF per unit length of fiber required is given by WF ϭ ЈP ϩ WFo (17) where P is the external pressure applied to the fiber mass; Ј is the equivalent frictional coefficient but with dimensions of length, and WFo is the value for WF when P ϭ 0, that is, the cohesion force. This conclusion has been utilized by Carnaby and Pan 75,86 to predict the compressional hysteresis and the shear modulus of fiber assemblies.…”
Section: The Coulomb Yield Criterion and The Fiber Pullout Forcementioning
confidence: 98%
“…On the other hand, the existing fiber contact point will also abate the free volume of the fiber mass, and consequently increase the chance for successive fibers to make new contacts. Some of the research results in this area have been applied to study the compressional 75,83 and shear 86 behavior of general fiber assemblies, as well as the prediction of nonwoven products, 77 leading to considerable progress in those areas.…”
Section: Fiber Packing Problemmentioning
confidence: 99%
“…The peak pressure p 0 is located at the center of the contact zone. By denoting a and b as the semi-axes of the ellipse of the contact zone, the peak pressure can be determined by (11) from which we have (12) In the above P is the compressive force that is actually the resultant adhesive force between two filaments in contact. The peak pressure is 1.5 times the average pressure on the contact surface, and a is related to the compressive force P and the semi-axes of the ellipse a and b [29] such that (13) where the semi-axes a and b are determined as (14) In the above, coefficients m and n are numbers depending only on the ratio (B -A) to (A + B) as tabulated in the literature [28].…”
Section: Problem Statement and Solutionmentioning
confidence: 99%